Perancangan User Interface pada Aplikasi Manajemen Usaha untuk UMKM Songket dengan Pendekatan Metode The Five Planes (Studi Kasus : Centra Tenun Tajung Palembang) - shendika dava; Ahmad Syazili (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
One of Palembang's traditional weaving industries (blongsong/tajung) is one of the mainstay industries in South Sumatra. The growth of the traditional weaving industry in Palembang city (blongsong/tajung) is quite rapid. Each industry has between 2 and 10 permanent and casual workers. In terms of utilizing technology, centra tenun tajung Palembang has not used technology for stock and financial management. Stock and financial management is still done manually by relying on Microsoft Excel and calculators. Whereas in this day and age, everyone has utilized technology to facilitate everything and achieve success. The Palembang tajung weaving center should have used the application in terms of stock and financial management. But before making an application the appearance of the application must be considered, especially from the user side. In this research, the author will create a user interface design on business management applications using the five plane method that applies five elements and test-ing. The result of this research is a User interface design prototype to be implemented in the management application system in the future. The use of the five plane method successfully creates a design that has a color combination that suits the needs and display that is easy to read by the user.